O processo de configuração curricular: uma análise da compreensão de professores de educação física das séries iniciais do ensino fundamental - Marques, Marcos Vinicius [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research deals with the curriculum themes and focuses on the Physical Education teacher of the initial series of elementary school. The objective is to analyze the understanding of teachers about their participation in the process that configures the curriculum, from dimensions of the school environment, their formation and the speech from teachers about teachers’ participation in curriculum. The study's theoretical framework the procedural approach to curriculum, which addresses the teacher's pedagogic practice, the relationship between curriculum and context, as well as the issue of teacher professionalization. Moreover, issues related are addressed to the history the curriculum, formation and teaching work and the relationship between physical education and curriculum in the initial series of elementary school. The research is qualitative and exploratory type, being held in a city in the state of São Paulo with nine teachers of Physical Education. The instruments are closed questionnaires and semi-structured interviews. The data are initially presented and divided into three categories, which then underwent a process of theorizing, in which, from the theoretical evidence, were propose new interpretations. The categories raised relate to the dimensions of the school environment and capacity to influence on teacher’s participation in curriculum; the relationship between formation and about the possibilities of such participation; and elements found in the speech of teachers over teacher’s participation in curriculum, which become concrete through the collective development of a model curriculum for Physical Education for the initial series of elementary school. From these aspects, new possibilities arise, which are represented in the proposal for a new schema about the process that configures the curriculum. Finally, we defend the need to consider the influence of the dimensions of the school environment and teacher education...

A presente pesquisa trata da temática do currículo e tem como foco o professor de Educação Física das séries iniciais do ensino fundamental. O objetivo do trabalho é analisar a compreensão dos professores de Educação Física sobre sua participação no processo em que se configura o currículo, a partir das dimensões do ambiente escolar, de sua formação e do discurso dos mesmos sobre a participação docente no currículo. O estudo tem como referencial teórico a abordagem processual do currículo, a qual aborda a prática pedagógica do professor, as relações entre currículo e contexto, bem como a questão da profissionalização docente. Além disso, na pesquisa, são tratados assuntos relacionados à história do currículo, à formação e ao trabalho docente e à relação entre Educação Física e currículo nas séries iniciais do ensino fundamental. A pesquisa é qualitativa do tipo exploratório, sendo realizada em uma cidade do interior de São Paulo com nove professores de Educação Física. Os instrumentos utilizados são questionários fechados e entrevistas semi-estruturadas. Os dados obtidos são, inicialmente, apresentados e divididos em três categorias, as quais, em seguida, são submetidas a um processo de teorização, no qual propomos novas interpretações. As categorias levantadas dizem respeito às dimensões do ambiente escolar e à capacidade de influência das mesmas sobre a participação docente no currículo; à relação entre a formação dos sujeitos e as possibilidades acerca desta participação; e aos elementos encontrados no discurso dos sujeitos sobre a participação docente no currículo, a qual se operacionalizaria através da elaboração coletiva de um modelo de currículo para Educação Física para as séries iniciais do ensino fundamental. A partir destes aspectos, surgem novas possibilidades, as quais estão representadas na proposta de um novo esquema acerca do processo em que se...
Keywords: Physical education and training - Study and teaching; Educação física - Estudo e ensino; Pratica de ensino; Ensino; Ensino - Curriculos; Ensino fundamental; Curriculos - Planejamento; Professores - Participação no planejamento curricular